Risk Governance Unlocks Islamic Banks’ Dual Performance Goals: Tata Kelola Risiko Mengungkap Tujuan Kinerja Ganda Bank Syariah - Kurniawan, Ferdian_Ari; Hanggraeni, Dewi; Purnomo, Gabriel (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the moderating effect of risk governance structures on the relationship between risk management—covering insolvency, financing, and operational risks—and the financial and social performance of Islamic banks in Indonesia. Using dynamic panel data regression, the analysis draws on annual report data from 11 Islamic commercial banks over the period from 2012 to 2021. The findings show that certain risk governance structures, such as the size and independence of the audit committee, the expertise of its members, the frequency of meetings, and the quality of external audits, significantly enhance the effectiveness of risk management in improving both financial and social outcomes. Moreover, unique Islamic banking structures, such as the size of the Shariah Supervisory Board and the frequency of its meetings, further strengthen these effects. These results highlight the importance of robust governance in optimizing risk management and improving the overall performance of Islamic banks, with implications for regulatory bodies and Islamic financial institutions aiming to improve governance frameworks.